The American Way of War : Guided Missiles, Misguided Men, and A Republic in Peril - Jarecki, Eugene (New York Free Press, 2008)
In the sobering aftermath of America's invasion of Iraq, documentarian Jarecki launches a penetrating inquiry into how forces within the American political, economic, and military systems have come to undermine the carefully crafted structure of our republic--upsetting its balance of powers, vastly strengthening the hand of the president in taking the nation to war, and imperiling the workings of American democracy. Surveying a scorched landscape of America's military adventures and misadventures, Jarecki's account includes interviews with leading figures in the Bush administration, Congress, the military, academia, and the defense industry. Their insights expose the deepest roots of American war making. As Jarecki powerfully argues, only concerted action by the American people can, and must, compel the nation back on course.--From publisher description.
Include Index and Notes.
Keywords: United States -- History, Military. -- United States -- Foreign Relations -- Philosophy